Soft Frequency Reuse (SFR) in LTE-A Heterogeneous Networks based upon Power Ratio Evaluation - Alvita Maurizka; F. Hamdani; M. M. Ulfah; Iskandar Iskandar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
As the traffic demand grows and the RF environment changes, the mobile network relies on techniques such as SFR in Heterogeneous Network (HetNet) to overcome capacity and link budget limitation to maintain user experience. Inter-Cell Interference (ICI) strongly affecting Signal-to-Interference plus Noise Ratio (SINR) of active UEs, especially cell-edge users, which leads to a significant degradation in the total throughput. In this paper we evaluate the performance of SFR with HetNet system in order dealing with interferences. Simulation result shows that the power ratio control in SFR HetNet system doesn’t have much effect on total achieved capacity for overall cell.